«Chores befitting her sex»: needlework and women’s education in Spain during the 19th century. Domesticity, art profession and gender construction - Hernández, Clara (Historia y Memoria de la Educación, 2022)
This paper analyses how the association between femininity and needlework was an important element in the gender construction process during the 19th century, and how this link produced a conflictive relationship between needlework and professionalization. To do so, it is firstly studied the role that sewing and embroidery had in girls’ education, as well as their assimilation to female nature and morality; secondly, its implementation in shaping femininity through visual and material culture; and ultimately, needlework professional aspect, adopting a broad perspective that includes industrial labour, craft and artistic work, along with its valuation in the frame of female work